PENINGKATKAN HASIL BELAJAR AKUNTANSI MELALUI MODEL PEMBELAJARAN KOOPERATIF - Agung Listiadi, ; Nelly Yuniaty Sitorus, (Pendidikan Ekonomi, 2010)
The current research is intended to examine the use of Number Head Together (NHT) of cooperative learning model to enhance the learning achievement of accounting lesson. This study is a classroom action research which consists of three cycles. It is found that Number Head Together (NHT) is able to increase the learning achievement of the students. This can be seen from the results of each cycle in which the learning achievement in cycle I reaches by  66,67%,  in cycle II 78,57%,  and cycle III 90,48%. Furthermore, the students showed positive response to the use of the NHT, which can be seen from the fact that 95,24% of the students enjoyed the NHT learning.